PENGARUH SARANA PRASARANA SEKOLAH DAN MOTIVASI BELAJAR SISWA TERHADAP PRESTASI BELAJAR SISWA PEMASARAN DI SMK NEGERI 1 SUKOHARJO TAHUN AJARAN 2015/2016 - Devi Ayu Kusuma Putri; Bambang Wasito Adi; Sunarto Sunarto (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
This research is aimed to know: (1) the school’s infrastructure affects the students’ learning achievement of Marketing students in SMK Negeri 1 Sukoharjo, (2) the students’ learning motivation affects the students’ learning achievement of Marketing students in SMK Negeri 1 Sukoharjo, (3) the school’s infrastructure and the students’ learning motivation affect the students’ learning achievement in SMK Negeri 1 Sukoharjo. This research quantitative research with descriptive methods. The population and sample of this research is the students of Marketing  and XI of SMK Negeri 1 Sukoharjo. The technique to determine the sampling used is proportional random sampling. The technique to collect the data is by using questionnaire and documentation. The technique of   analyzing the data is by using double regression, T-test and f-test.Based on the result of this research, it can be concluded that: (1) there is an effect of the school’s infrastructure toward the students’ learning achievement of Marketing students in SMK Negeri 1 Sukoharjo,  (2) there is an effect of the students’ learning motivation towards the students’ learning achievement of Marketing students in SMK Negeri 1 Sukoharjo, (3) there is an effect of the school’s infrastructure and the students’ learning motivation toward the students’ learning achievement of Marketing students in SMK Negeri 1 Sukoharjo.